Targeted PET/MRI Imaging Super Probes: A Critical Review of Opportunities and Challenges - Kastelik-Hryniewiecka, Anna; Jewula, Pawel; Bakalorz, Karolina; Kramer-Marek, Gabriela; Kuźnik, Nikodem (International journal of nanomedicine, 2021)
Recently, the demand for hybrid PET/MRI imaging techniques has increased significantly, which has sparked the investigation into new ways to simultaneously track multiple molecular targets and improve the localization and expression of biochemical markers. Multimodal imaging probes have recently emerged as powerful tools for improving the detection sensitivity and accuracy-both important factors in disease diagnosis and treatment; however, only a limited number of bimodal probes have been investigated in preclinical models. Herein, we briefly describe the strengths and limitations of PET and MRI modalities and highlight the need for the development of multimodal molecularly-targeted agents. We have tried to thoroughly summarize data on bimodal probes available on PubMed. Emphasis was placed on their design, safety profiles, pharmacokinetics, and clearance properties. The challenges in PET/MR probe development using a number of illustrative examples are also discussed, along with future research directions for these novel conjugates.
Keywords: contrast agents; multimodální zobrazování; Multimodal Imaging; clearance; Positron-Emission Tomography; pozitronová emisní tomografie; medical imaging; targeting; relaxivity; bioresponsive probes; magnetická rezonanční tomografie; Magnetic Resonance Imaging